Diseño e implementación de una red de comunicación inalámbrica para protección ambiental en el bosque - Navarro-Murillo, Emmanuel (Instituto Tecnológico de Costa Rica, 2005)
Now days the preservation of the natural resources have taken a big importance in our country and the world in general. The Costa Rican forests are been threat by illegal practices, like hunting, deforestation and forest fires. That’s why it come the idea to use the electronic knowledge to create a wireless sensor network to monitor these kinds of activities. The goal of this project is to develop a monitor tool that allows the communications between different zones in the forest, so when an alarm is activated, the authorities can perform on time their respective action. Costa Rica has always been internationally famous for his protected zones, making the tourism one of the major incomes for the country and a healthy environment for the people who lives on it. There is the importance of the project since it’s necessary to avoid the irrational exploitation of the natural resources of the country in order to give them to the future generations and they’re a source of income to the national economy. The focus of the project is based on the solution for the wireless communication of the monitor system. It contemplates the hardware and the network protocols. This protocol sees the network like a series of logical levels, so the base is going to be in a cero level and when the distance of the teledetectors increases, the level is going to increase too. When an alarm is activated, the information is going to flow to the lower levels until it reaches the cero level.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2005.
Keywords: Hardware; Software; Redes inalámbricas; Transmisión; Sensores; Modulación; Interfaz